Analysis of the Influence of Leadership, Compensation and Work Environment on Employee Performance (Case Study at PT. Lakawan) - Karman, Abd (AL-QARDH, 2022)
This study aimed to examine and analyze the influence of leadership, compensation, and work environment on employee performance either partially or simultaneously between variables. This type of research is explanatory with a quantitative research approach. The population in this study were all employees of PT. Lakawan is 125 people with a total sample of 95 employees. The technique used in sampling is purposive sampling. The analytical tool used is SPSS with classical assumptions and multiple regression. The results of the study prove that there is a positive influence between leadership on employee performance, the better the leadership, the higher the employee performance. A positive effect of compensation on employee performance was also found, which means that giving appropriate compensation will have an impact on increasing employee performance. Then the work environment variable also found a positive influence on employee performance, meaning that the more comfortable the employee is in the work environment, the better the performance will be. While the variables of leadership, compensation, and work environment together, were found to be able to improve the performance of employees of PT. Come on. The most dominant variable contributing to employee performance is the work environment.